2023
DOI: 10.3390/genes14091798
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms within the SARS-CoV-2 Human Receptor Genes Associate with Variable Disease Outcomes across Ethnicities

Theolan Adimulam,
Thilona Arumugam,
Anushka Naidoo
et al.

Abstract: The contribution of human genes to the variability of disease outcomes has been shown to be important across infectious diseases. Studies have shown mutations within specific human genes are associated with variable COVID-19 outcomes. We focused on the SARS-CoV-2 receptors/co-receptors to identify the role of specific polymorphisms within ACE2, TMPRSS2, NRP1 and CD147. Polymorphisms within ACE2 (rs2285666), TMPRSS2 (rs12329760), CD147 (rs8259) and NRP1 (rs10080) have been shown to associate with COVID-19 sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Gene polymorphisms within the receptors/co-receptors of SARS-CoV-2, including NRP1 (rs10080), were reported to associate with variable COVID-19 outcomes across ethnicities [17,18]. Mutating NRP1 novel interaction sites, located in the vestigial plasminogenapple-nematode (PAN) domain, were recently reported to reduce the S-protein of SARS-CoV-2 internalization [19], although another reported that the binding affinity is almost the same after mutation at some NRP1 sites (rs141633354, rs142121081, rs145954532, rs200660300, rs200028992, rs369312020, rs370551432, rs370641686, and rs370117610) via molecular docking [20].…”
Section: Introductionmentioning
confidence: 99%
“…Gene polymorphisms within the receptors/co-receptors of SARS-CoV-2, including NRP1 (rs10080), were reported to associate with variable COVID-19 outcomes across ethnicities [17,18]. Mutating NRP1 novel interaction sites, located in the vestigial plasminogenapple-nematode (PAN) domain, were recently reported to reduce the S-protein of SARS-CoV-2 internalization [19], although another reported that the binding affinity is almost the same after mutation at some NRP1 sites (rs141633354, rs142121081, rs145954532, rs200660300, rs200028992, rs369312020, rs370551432, rs370641686, and rs370117610) via molecular docking [20].…”
Section: Introductionmentioning
confidence: 99%